Media Sosial Youtube unntuk Meningkatkan Kemampan Bahasa Inggris dan Matematika pada Anak Usia Dini - Sinta Sinta; Maya Saftari (Journal on Education, 2023)
The easier it is to use YouTube social media that can be accessed by children to the elderly, making everyone's visual motor skills able to remember, especially in early childhood. As we know that children who hone their visual motor skills will be able to record and recall what they have seen and heard. YouTube social media makes it easy for parents to get used to their children learning while watching. By using the method of observation and interviews with working parents and children, the average success in getting children used to learning foreign languages, namely English and basic mathematics, so that children get used to it and easily learn these abilities. By using YouTube social media, it makes children love English and mathematics even more from an early age because English and mathematics are basic sciences that all ages must learn. This basic knowledge is very supportive to enter every level of education and work. Keywords: youtube social media, foreign language, basic matgematics